Pre-delivery remifentanil infusion for placenta accreta cesarean delivery under general anesthesia: an observational study. (1st September 2016) - Shaylor, R.; Ginosar, Y.; Avidan, A.; Eventov-Friedman, S.; Amison, N.; Weiniger, C. F.
Abstract: Objective : General anesthesia may be required for placenta accreta cesarean delivery. Intrauterine fetal anesthetic exposure should be minimized to avoid neonatal respiratory depression; opioids are often delayed until post-delivery. Methods : In this observational study, we compared neonatal outcome using pre-delivery remifentanil versus post-delivery (deferred) opioids for placenta accreta cesarean delivery. Choice of anesthesia was discretionary. The primary outcome was Apgar score at 5 min comparing women who received pre-delivery remifentanil versus deferred opioid administration. We recorded maternal/obstetric characteristics, surgical characteristics, maternal hemodynamic data, neonatal outcomes: Apgar scores, umbilical vein pH and respiratory interventions at birth. Results : Between February 2007 and April 2014 we identified 40 general anesthesia placenta accreta cesarean deliveries. The remifentanil dose rate ranged from 0.06 to 0.46 mcg kg −1  min −1 . Obstetric and maternal characteristics were similar. Neonatal Apgar, umbilical pH and respiratory intervention outcomes were similar in both groups; Apgar scores median (interquartile range IQR [range]) at 5 min were 9 (8–10) for pre-delivery remifentanil versus 9 (9–10) for deferred opioid administration, p  = 0.18. Conclusions : We did not observe a significant effect on neonatal Apgar scores at 1 and 5 min, or respiratory interventions at birth when remifentanil infusion was administered pre-delivery.